2022
DOI: 10.21203/rs.3.rs-2277227/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cx43 promotes exocytosis of damaged lysosomes through actin remodelling

Abstract: A robust cellular response to lysosomal membrane damage is essential to prevent lysosomal content leakage to the cytoplasm and subsequent activation of cell death pathways. Here we report exocytosis as an important response mechanism to lysosomal damage, which is further potentiated when membrane repair or lysosomal degradation mechanisms are impaired. Our data reveal that Connexin43 (Cx43), a protein canonically associated with gap junctions, is recruited to damaged lysosomes to promote their secretion, there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 95 publications
(77 reference statements)
2
3
0
Order By: Relevance
“…Here, we found that Cx43 is recruited to the expanding phagosome and promotes hyphal fold, possibly by anchoring Arp2. These findings are in accordance with our recent work showing that Cx43 is recruited to damaged lysosomes and promotes exocytosis through the remodeling of actin cytoskeleton ( 44 ). In this process, we found that Cx43 effect on actin rearrangement is dependent on Arp2 activity ( 44 ).…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…Here, we found that Cx43 is recruited to the expanding phagosome and promotes hyphal fold, possibly by anchoring Arp2. These findings are in accordance with our recent work showing that Cx43 is recruited to damaged lysosomes and promotes exocytosis through the remodeling of actin cytoskeleton ( 44 ). In this process, we found that Cx43 effect on actin rearrangement is dependent on Arp2 activity ( 44 ).…”
Section: Discussionsupporting
confidence: 94%
“…These findings are in accordance with our recent work showing that Cx43 is recruited to damaged lysosomes and promotes exocytosis through the remodeling of actin cytoskeleton ( 44 ). In this process, we found that Cx43 effect on actin rearrangement is dependent on Arp2 activity ( 44 ). Additionally, supporting our hypothesis, components from this actin nucleator protein were also identified in our STRING analysis, namely, actin-related protein 2/3 complex subunit 5 (ARCP5), a component of the Arp2/3 complex, and actin-related protein 2 (ACTR2), an ATP-binding component of the Arp2/3 complex, promoter of branched actin networks.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations